probability & statistics for engineers & scientists Eight edition - Walpole, Ronald E; Myers, Raymond H; Myers, Sharon L; Ye, Keying (New Jersey, USA Pearson Education, 2007)
This comprehensive introduction to probability and statistics will give you the solid grounding you need no matter what your engineering specialty. Through the use of lively and realistic examples, the author helps you go beyond simply learning about statistics to actually putting the statistical methods to use. Rather than focus on rigorous mathematical development and potentially overwhelming derivations, the book emphasizes concepts, models, methodology, and applications that facilitate your understanding
"Not for sale in USA or canda"
"Pearson international edition"
Keywords: Civil engineering; Logic; Nature study; Probabilities; Statistics